Evaluation of Land Suitability for Agroforestry Development Based on Liberika Coffee in Kedabu Rapat Village, Meranti Islands Regency - Fransius Brinel Bangun; Wawan Wawan; Nurul Qomar (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
Land evaluation is the process of comparing a series of data on land, vegetation and climate with specific use requirements. The goal to be achieved is to determine land use options as a bridge between physical, biological and technological components with economic goals to be achieved in a particular form of land use. Agroforestry is an integrated land use system, which has social and ecological aspects, implemented by combining trees with agricultural crops and / or livestock (animals), either jointly or in rotation. This study aims to identify land characteristics, evaluate the level of land suitability and how to develop a combination pattern of agroforestry plants based on Liberika Coffee that is right for the sake of improving the economy of the community in Kedabu Rapat Village. The method used is survey method and soil sampling by transect line at 1 kilometer intervals proportionally. The data analysis performed was scoring and matching between land characteristics and quality data with plant growth requirements using ArcGIS 10.2 software. The results showed that the annual average rainfall was 1,200-2,400 mm / year, temperatures were between 25 ° C - 32 ° C, flat topography with a classification of slope (<3%), soil types were Organosols and Gleihumus, flood hazard from none to moderate and the danger level of landslides and erosion is very light or not prone. The land suitability level for agroforestry based on Liberika Coffee with shade in the form of Coconut, Areca nut and Geronggang plants is very suitable (S1) covering an area of ​​± 848.64 ha (34.78%), the appropriate category (S2) covering an area of ​​± 584.54 ha (23, 96%), the category according to marginal (S3) is ± 521.78 ha (21.38%), and the unsuitable category (N) is ± 380.42 ha (15.59%) while the settlement area is ± 104.61 ha (4.29%). The combination pattern of agroforestry plants based on Liberika Coffee with shade plants of Coconut, Pinang and Geronggang in Kedabu Rapat Village is combination pattern 1 (border tree planting / trees along border) and combination pattern 2 (alley cropping) where Liberika Coffee plants are 2.5 x spacing. 2.5 m, Coconut spacing 10 x 10 m, Pinang spacing 2.5 x 2.5 m and Geronggang spacing 5 x 5 m.